Model Variations and Automated Refinement of Domain-Specific Modeling Languages for Robot-Motion Control - Djukić, Verislav; Popović, Aleksandar; Luković, Ivan; Ivančević, Vladimir (Computing and Informatics, 2019)
This paper presents an approach to handling frequent variations of modeling languages and models. The approach is based on Domain-Specific Modeling and linking of modeling tools with adaptive Run-Time Systems. The applicability of our solution is illustrated on an example of domain-specific languages for robot control. Special attention was given to the following problems: 1) model-level debugging; 2) performing fast transformation of models to native code for various hardware platforms and operating systems; and 3) specification of views and view-based generation of applications for validation of meta-models, models, and generated code. The feedback for automated refinement of models and meta-models is provided by a custom adaptive Run-Time System. For the purpose of synchronizing models, meta-models, and the target Run-Time System, we introduce action reports, which allow model-level debugging. In order to simplify handling of frequent model variations, we have introduced the linguistic concept of a modifier.